STRATEGI KUALITAS PRODUK, WORD OF MOUTH (WOM) DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN UMKM RUMAH ROTI SURABAYA - Emmywati ,; Bagus Ardianto (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2019)
This study aims to determine the product quality, word of mouth and price perceptions of customer satisfaction both simultaneously and partially on MSME customers. housing and the neighboring villages in the past 6 months. While the technique used in this study is Nonprobability Sampling with incidental sampling technique that is taking samples based on approval, anyone who agrees to be found is taken according to the data source with a total sample of 100 respondents. Data collection techniques using questionnaires. The data analysis technique used in this study is multiple linear regression analysis using the IBM SPSS 20. The results of the study show that: 1) product quality variables, word of mouth and price perception are related simultaneously or together to MSME customer satisfaction Surabaya Bread House. 2) product quality variables, word of mouth and price perception of partial to Rumah Roti SME customer satisfaction.